Recalibrating ancient mythology for contemporary performance: the Mises en scène of the Mahabharata by Peter Brook and Les Atrides by Ariane Mnouchkine - Glynn, D (2011)
There is consensus in academic circles that the directors Peter Brook and Ariane Mnouchkine have similar approaches to theatre practice and occupy the same position in the landscape of theatre production in France. Yet there have not been any in-depth studies that unpack the similarities and differences between the two practitioners. Considering their stature on the national French and international stages, such a gap of scholarship needed to be filled. By examining the specificities of their practices via the analysis of their two most emblematic productions, the Mahabharata and Les Atrides, this thesis hopes to provide an appraisal of their practices at a time when they are moving away from theatre. More specifically, this thesis looks at how the two directors transferred ancient archetypal and mythological narratives to the contemporary French stage. It considers how they used successful, parallel methodologies to adapt and render present an Ancient Sanskrit epic on the one hand (Brook), and Ancient Greek drama on the other (Mnouchkine). I uncover in their work the matrix for adaptation, located in the discourse of storytelling and in the post-Brechtian concept of estrangement, that I label ‘décalage’. Moreover, the thesis hopes to provide an appraisal of the supremacy of directors on the French stage in the nineteen eighties and advocates for the cultural necessity of theatre as an art form, at a time of crisis in France.